KINERJA KEUANGAN DENGAN PENDEKATAN PEARLS PADA KOPERASI CITRA AKADEMIKA DI KUPANG - Sesilia Roswita De Ornay; Petrus E. de Rozari; Hironnymus Jati (Journal of Management Small and Medium Enterprises (SMEs), 2018)
This research is aim to know the financial performance with PEARLS approach on Citra AkademikaCooperation in Kupang in 2013 to 2017 in terms of aspects of Proctetion, Effective Financial Structure,Asset Quality, Rate of Return and Cost, and Sign of Growth. The research was done from May to June2018. The data that used are financial statements of cooperation by calculating 35 ratio of PEARLS.The data collected through interviews and documentation. The data analysis technique performed toanswer this analysis by using PEARLS.The result of this research shows that financial performance atCitra Akademika Cooperation is viewed from aspect (1) Proctetion as a whole shows ideal result withadequate risk reserve factor (2) Effective financial structure as a whole shows ideal result because it canincrease growth potential and earning capacity based on investment (3) The overall asset quality showsthe ideal result because it is able to suppress the ratio of problems that occur in the given loan (4) Rate ofreturn and cost (rate of income and expense) overall shows the ideal result because it is able to provideincome and expenses also measure the average earning income productively. (5) Liquidity indicates theresult is not ideal because it is unable to provide liquid cash reserves to meet the demand for loansgranted from non-stock deposits (6) Sign of growth (signs of growth) as a whole shows the ideal resultwith adequate asset growth. Citra Akademika Cooperation needs to consider the analyzing of financialstructure so that in the coming year the financial performance of Citra Akademika Cooperation can becategorized as a healthy cooperation, in order to increase the asset quality of the cooperation andconduct supervision to the costs to be incurred by each part of the cooperation in order to increase thegrowth of cooperation to be healthy.Keywords: PEARLS, Financial performance